Stress Distribution in Co-Cr Implant Frameworks after Laser or TIG Welding - Castro,Gabriela Cassaro de (2013)
Lack of passivity has been associated with biomechanical problems in implant-supported prosthesis. The aim of this study was to evaluate the passivity of three techniques to fabricate an implant framework from a Co-Cr alloy by photoelasticity. The model was obtained from a steel die simulating an edentulous mandible with 4 external hexagon analog implants with a standard platform. On this model, five frameworks were fabricated for each group: a monoblock framework (control), laser and TIG welding frameworks. The photoelastic model was made from a flexible epoxy resin. On the photoelastic analysis, the frameworks were bolted onto the model for the verification of maximum shear stress at 34 selected points around the implants and 5 points in the middle of the model. The stresses were compared all over the photoelastic model, between the right, left, and center regions and between the cervical and apical regions. The values were subjected to two-way ANOVA, and Tukey's test (α=0.05). There was no significant difference among the groups and studied areas (p>0.05). It was concluded that the stresses generated around the implants were similar for all techniques.